Enhancing Idiomatic Competence through WhatsApp: A Comparative Study of Mobile and Traditional Teaching Methods - Batubara, Riska Widiyanita; Batubara, Amrin; Ardiyansah, Tri Yuli (Jurnal Evaluasi dan Pembelajaran, 2024)
This study examines the effectiveness of using WhatsApp as a tool for teaching English idiomatic expressions to pre-intermediate EAP students in the Non-English Department at the University of Muhammadiyah Gresik. From a pool of 250 students, 64 participants were selected based on their English proficiency using the Nelson Quick Check Placement Test and divided into experimental and control groups. The experimental group received idiom lessons and exercises through a WhatsApp group called Idiom Learning Group. They practiced 60 idioms outside the classroom, interacted with the researcher, and could make WhatsApp video calls for additional clarification. In contrast, the control group received the same lessons through traditional face-to-face instruction. The study was conducted over nine sessions. The first two sessions involved administering the placement test and a pre-test on idiomatic competence. The treatment phase spanned six sessions, during which the experimental group used WhatsApp for instruction and practice while the control group engaged in in-class learning. In the final session, both groups took a post-test to measure their improvement in idiomatic competence. Data analysis using paired samples and independent samples t-tests revealed a significant difference in post-test scores between the two groups, with the experimental group significantly outperforming the control group (p < .05). The findings demonstrate that teaching idioms through mobile technology, specifically WhatsApp, enhances idiomatic competence more effectively than traditional methods. This suggests that integrating mobile technology into language teaching can provide learners with flexible, interactive, and engaging opportunities for language practice, ultimately improving their learning outcomes.